California streamin' : developing an integrated social media strategy to attract fans to a new streaming app - Ingerson, Lynley; Naraine, Michael L., 1987-; Agha, Nola; Pedroza, Daniel J. (London : Human Kinetics, Inc., 2020)
Laurie Spinks is the Director of Social Engagement at NBC Sports Bay Area. She has been instrumental in developing strategies for social media platforms across a number of different sports, and must now develop a social media strategy which drives fans towards a new app. NBC Sports created the My Teams app to counter cord-cutting and allow sport fans to stream live games of their favorite local teams on their mobile devices. Prior to the launch of the app in the Bay Area, Spinks will meet with her team to formulate a social media strategy which supports the new app. This case explores some of the elements that contribute to the development of a social media marketing strategy for the NBC Sports My Teams app. In particular, the strategy focuses on targeting the San Francisco Bay Area sport audience by identifying and developing social media objectives, creating an audience profile for app usage, and implementing appropriate strategies to support objectives and attract the desired audience.
Originally Published InIngerson, L., Naraine, M. L., Agha, N. & Pedroza, D. J. (2020). California Streamin': Developing an Integrated Social Media Strategy to Attract Fans to a New Streaming App. International Journal of Sport Communication, 9(S1), S13-S19.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Streaming video -- Marketing -- Case Studies; Social media -- Case Studies